2019
DOI: 10.18052/www.scipress.com/ilns.76.72
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria and Glutathione Applications Improve Productivity, Nutrient Contents, and Antioxidant Systems of Salt-Stressed Soybean Plant

Abstract: Salt stress restricts plant performance by disrupting various physio-biochemical processes like photosynthesis. Plants growing in saline substrates show deficiencies in absorption of some essential elements due to the presence of excessive sodium (Na+) in the rhizosphere, which antagonizes beneficial cations and causing toxicity in metabolism. Cyanobacteria (CB; a natural biofertilizer) play a fundamental role in building-up soil fertility, thus increasing plant performance. Glutathione (GSH) is a well-known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
(62 reference statements)
2
6
0
Order By: Relevance
“…These positive results examined in this study were positively reflected in maize plant growth and dry matter accumulation ( Figure 1 , Table 6 ). Our findings are consistent with those in [ 2 , 5 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Restoration of growth and dry matter accumulation of Cd-stressed maize plants are also due to the positive impacts of proline, AsA, and GSH present in MEg-Sm on increasing hormones (e.g., IAA, GA 1 , GA 3 , cytokinins including trans-zeatin, SA) content and homeostasis, which are necessary to restore the developmental growth of stressed plants [ 20 , 23 , 60 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These positive results examined in this study were positively reflected in maize plant growth and dry matter accumulation ( Figure 1 , Table 6 ). Our findings are consistent with those in [ 2 , 5 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Restoration of growth and dry matter accumulation of Cd-stressed maize plants are also due to the positive impacts of proline, AsA, and GSH present in MEg-Sm on increasing hormones (e.g., IAA, GA 1 , GA 3 , cytokinins including trans-zeatin, SA) content and homeostasis, which are necessary to restore the developmental growth of stressed plants [ 20 , 23 , 60 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the major growth stimulators present in MEg-Sm, proline, AsA, and GSH contents were greatly increased in Cd-stressed plants and contributed to stabilizing and maintaining cell membranes against stress damage [ 2 , 5 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. These positive effects of these antioxidants might be attributed to their roles in minimizing the Cd content or other toxic elements and the levels of oxidative stress markers (O 2 • − and H 2 O 2 ; Figure 2 , Table 6 ), thus minimizing lipid peroxidation in cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in accordance with numerous other reports for different plant species such as maize (Thajuddin & Subramanian, 2005) and rice (Prasanna et al, 2012). The enhancement of maize growth may be related to the ability of CB to supply the plants by several nutrients, in addition to lowering soil pH that may promote soil nutrient availability (Zaki et al, 2019). Khalil & El-Noemani (2015) suggested that CB improves soil chemical properties and strengthen biological and physical characters which represent supportive factors for root development.…”
Section: Discussionsupporting
confidence: 92%
“…It can prevent water loss or preserve leaf RWC (Abd El-Mageed et al, 2018). Respectively, Merwad et al (2018) and Zaki et al (2019), using the soybean and cowpea plants, reported the highest levels of proline and soluble sugars by exogenous GSH under drought and saline treatments.…”
Section: Discussionmentioning
confidence: 99%